Knee pain and functional disability of knee osteoarthritis patients seen at Malaysian government hospitals - Foo, Chai Nien; Arumugam, Manohar; Gyanchand Rampal, Lekhraj Rampal; Lye, Munn Sann; Mohd Sidik, Sherina; Jamil @ Osman, Zubaidah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2017)
Introduction: Osteoarthritis (OA) is the main cause of knee pain. It also affects individual’s physical functioning. Anti- inflammatory drugs and knee replacement are the mainstay methods in the management of knee OA in Malaysia. However, patients with knee OA often suffer pain. The general objective of the study is to evaluate the effectiveness of a cognitive behavioural intervention module on knee pain, functional disability and psychological outcomes among knee OA patients attending Orthopedics Clinics in Hospital Putrajaya and Hospital Serdang, Malaysia. This study aims to determine the baseline level of knee pain and functional disability among knee OA patients. Methods: Baseline results on the knee pain and functional disability were obtained from a two arm parallel- group randomized controlled study. Three hundred patients aged 35 to 75 years diagnosed with knee OA were recruited. A set of pre tested and validated Knee injury and Osteoarthritis Outcome Score (KOOS) questionnaire was used in this study. Results: Mean baseline of KOOS pain was 56.09 (SD=21.75) and 52.26 (SD=22.08) for the intervention and control groups respectively. Participants in the intervention and control groups had a mean KOOS function in daily living of 61.11 (SD=21.20) and 56.72 (SD=22.13) respectively. Overall mean baseline of KOOS function in sport and recreation was 35.30 (SD=27.38). Conclusions: Majority of participants had moderate level of knee pain and functional disability in daily living. However, participants had more extreme symptoms of functional disability in sport and recreation. Therefore, interventions to reduce knee pain and functional disability symptoms in knee OA are needed.